Lucian's satire or philosophy on sale - Pinheiro, Marília P. Futre (Revista Archai, 2015)
Famous philosophers and their conceits became the target of Lucian's satirical verve in many of his works. However, in Philosophies for Sale (Auctio Vitarum), Lucian offers an original view of philosophy. Just like a marketing expert would, Lucian treats philosophy as a product that is designed to satisfy the customers' needs, and whose nature is decisively influenced by consumer forces. My discussion is inspired by the main analytic tools and the basic core concepts of marketing. I argue that in Philosophies for Sale Lucian revolutionized the established concept that philosophy as well as human sciences in general are not governed by market rules. On the contrary, he has shown that philosophy, just like any other activity involving a trade of values between two parties, can be assessed from an economic perspective and that, consequently, must be viewed as customer-creating value satisfactions, being subject to the law of supply and demand.